(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the results of some interventions to protect and improve the health of female workers at two industrial garment companies in Thai Binh city. Research subjects and methods: The study was conducted with two research designs suitable for two phases including a descriptive epidemiological study through a cross-sectional survey and a controlled community intervention study on female workers at two industrial garment companies. Results: The rate of female workers with good general knowledge before the intervention was 28.2% and after the intervention was 75.1%. The intervention effect on general knowledge of workers in both intervention and non-intervention groups was 166.3%. The rate of workers with good general practice before the intervention was 9.8% and after the intervention increased by 25.1%. The intervention effect on good general practice of workers in both intervention and non-intervention groups was 156.1%. After the intervention, the rate of cardiovascular disease decreased by 58.1%, the rates of skin diseases decreased by 75.9%; musculoskeletal diseases by 35.0% and ear, nose and throat diseases by 33.0%. The rate of workers with health classification level I before the intervention was 7.6% and after the intervention increased by 25.6%. The intervention effect on health classification level I in female workers in the intervention and control groups was 180.3%. Conclusions: After the intervention, the knowledge and practice of occupational safety and hygiene among female workers were improved. The rate of disease after the intervention decreased and the number of female workers with health classification level I increased. Therefore, it is necessary to regularly train and test the knowledge and practice of occupational safety and hygiene of female workers.